2010
DOI: 10.1002/jcla.20364
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of delta value of platelet parameters on ADVIA 120 for the functional reactivity of stored platelets

Abstract: An agonist-induced expression of CD62P by flow cytometry analysis for evaluating platelet functional reactivity has some disadvantages. We investigated the usefulness of platelet parameters by ADVIA 120 to predict an agonist-induced expression of CD62P in stored platelets. The CD62P expression by flow cytometry and the platelet parameters by ADVIA 120 were studied in samples from 27 platelet pheresis products. Delta (D) values were calculated as the degree of change of the platelet parameters studied with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Several studies have recently demonstrated that MPC values are inversely correlated with PLT membrane activation and subsequent P‐selectin expression . In fact, the MPC variable has been used as an indicator of PLT activation in different conditions and physiologic states,28‐31 as well as stored PCs . In the present study, we observed that MPC decreased during 7‐day PLT storage indicating PLT activation in the three arms of the study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Several studies have recently demonstrated that MPC values are inversely correlated with PLT membrane activation and subsequent P‐selectin expression . In fact, the MPC variable has been used as an indicator of PLT activation in different conditions and physiologic states,28‐31 as well as stored PCs . In the present study, we observed that MPC decreased during 7‐day PLT storage indicating PLT activation in the three arms of the study.…”
Section: Discussionsupporting
confidence: 56%
“…27 In fact, the MPC variable has been used as an indicator of PLT activation in different conditions and physiologic states, [28][29][30][31] as well as stored PCs. 25,32,33 In the present study, we observed that MPC decreased during 7-day PLT storage indicating PLT activation in the three arms of the study. However, higher MPC indicating lower PLT activation was seen in PCs prepared with the Atreus 3C and suspended in PAS-IIIM when compared with the other two arms of the study.…”
Section: Discussionsupporting
confidence: 54%
“…This study showed that PCDW correlated with CD62P expression during 5 days of storage, but there was no correlation between MPC and CD62P. Other investigators [10] showed a negative correlation between CD62P and the change in PCDW (from the time zero value), in stored apheresis platelets anticoagulated with Acid Citrate Dextrose (ACD) and activated with adenosine diphosphate (ADP). However, neither of these studies incorporated the addition of extra anticoagulant to the platelet concentrate samples.…”
Section: Introductionmentioning
confidence: 56%
“…Decrease in MPC and increase in MPV are reliable indicators of platelet activation, because activation of these cells is associated to cell degranulation and cell swelling, respectively (24). Mean MPC significantly decreased in a similar manner in ACP® after both storage processes.…”
Section: Tab 2 Deskriptive Werte Der Konzentration An Plateletmentioning
confidence: 96%
“…Platelets are prone to activation, which induces an increase in their size, shape alterations and a decrease in their cellular density (36,37). Their activation level can be objectively measured with laser flow cytometry to determine their volume (mean platelet volume, MPV) and refractive index (mean platelet component, MPC) (24). Exogenous platelet activation techniques, such as addition of collagen, thrombin, calcium chloride or combinations thereof (25,37,41), show dose-dependent effects (18), but they might also induce undesirable inflammatory reactions (38).…”
Section: Introductionmentioning
confidence: 99%